(untitled) (Web of Teachers: Inderscience Research, 2024)
This article will cover the most important aspects of volleyball players’ nutrition. Volleyball is a game that requires a lot of strength and energy. During the game, volleyball players often jump and make sharp accelerations. For the proper functioning of the body, a balanced diet is required, which helps athletes to be in good energy shape before important games and serious workouts.